Studi Diagnostik Tingkat Penerapan Kultur Teknis Kelapa Sawit Dalam Upaya Peningkatan Kesejahteraan Pekebun Sawit Swadaya: Studi Kasus Kabupaten Padang Lawas Utara - Zulfi Prima Sani Nasution (Inovasi, 2019)
In line with the growth of independent smallholders, efforts to increase their productivity and sustainability are now a concern for policymakers. The main obstacle faced by independent smallholders is the low yield, as experienced by independent smallholders in North Padang Lawas District, North Sumatra. This study aimed to determine the current conditions of oil palm cultivation practices and develop policy recommendations to increase oil palm yield in North Padang Lawas District. The study was carried out through surveys and in-depth interviews involving 40 independent smallholders spread across the sub-district of Padang Bolak, Portibi, Halongonan, and Halongonan Timur. The results showed that lack of knowledge about oil palm legitimate seeds and standard practices of oil palm cultivation had caused the actual yield was only half of the potential yield of land suitability S3, especially for independent smallholders in the sub-district of Padang Bolak, Portibi, and Halongonan Timur. In addition, the process of selling fresh fruit bunches (FFB) that were not managed through farmer organizations (groups or cooperatives) caused a long chain of FFB marketing, thereby reducing the smallholder's income. Limited access to finance from banks burdened smallholders in implementing standard practices of oil palm cultivation, especially fertilization. Strengthening the role of local governments, banks and plantation companies are expected to change the mindset of smallholders regarding the importance of using legitimate oil palm seeds, adopting the best practices of oil palm cultivation, opening access to finance, and strengthening smallholders institutions so that the welfare and sustainability of independent smallholders in North Padang Lawas District can be realized soon.